Bangladesh national culture and heritage : an introductory reader - Ahmed, A. F. Salahuddin; Chowdhury, Bazlul Mobin; Khan, A. Majeed; Chowdhury, Abdul Momin; Shahed, Syed Mohammad; Independent University, Bangladesh (Dhaka : University Press Limited, 2022)
Contributed articles on history and civilization of Bangladesh in 19th and 20th century.
Includes bibliographical references and index.
GenEd (RS)
Development Book Agency, Karim International, Book Finder International.
Keywords: Bangladesh -- History -- 19th century; Bangladesh -- History -- 20th century; Bangladesh -- Civilization -- 20th century; Bangladesh -- Civilization -- 19th century